2019
DOI: 10.1080/15732479.2019.1615962
|View full text |Cite
|
Sign up to set email alerts
|

Use of gaming technology to bring bridge inspection to the office

Abstract: This paper proposes a novel method for bridge inspection that essentially digitises bridges using Light Detection and Ranging (LIDAR) so that they can be later inspected in a virtual reality (VR) environment. The work uses conventional terrestrial LIDAR together with affordable VR hardware and freely available software development kits originally intended for authoring computer games. The resulting VR app is evaluated for a case study involving a typical masonry bridge, comparing the proposed technique with tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 28 publications
0
34
0
Order By: Relevance
“…This type is mainly used to provide an immersive environment for its user, leaving his or her hands free to interact with the real environment. There are two main subtypes of HMD that can be found in the literature: the optical and/or video see-through HMDs, which let the user see the real-word with immersive augmentations [25,26,43,47,66,67,[70][71][72][73]75,78,80] (see Figure 6b), and the occluded HMDs, where the user is entirely immersed in a virtual environment [25,47,75,78,79] (see Figure 6c). While the occluded HMDs are mainly seen as VR devices, the see-through HMDs are mostly used for AR and MR applications.…”
Section: Main Devices Used For Visualisationmentioning
confidence: 99%
See 3 more Smart Citations
“…This type is mainly used to provide an immersive environment for its user, leaving his or her hands free to interact with the real environment. There are two main subtypes of HMD that can be found in the literature: the optical and/or video see-through HMDs, which let the user see the real-word with immersive augmentations [25,26,43,47,66,67,[70][71][72][73]75,78,80] (see Figure 6b), and the occluded HMDs, where the user is entirely immersed in a virtual environment [25,47,75,78,79] (see Figure 6c). While the occluded HMDs are mainly seen as VR devices, the see-through HMDs are mostly used for AR and MR applications.…”
Section: Main Devices Used For Visualisationmentioning
confidence: 99%
“…This benefit also seemed to be reinforced when the operator's position and orientation, relative to that of the equipment, are considered to hide or display the information. Some authors have also observed that VR devices can be used to perform inspection in the virtual environment [79], allowing remote stakeholders to provide their expertise on it. The use of artificial lighting on a 3D representation of the inspected element could help to identify otherwise hard-to-see damage (see Figure 10).…”
Section: Maintenance Improvementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Those studies are being supported by others aimed at integrating different tools and methods for an in-depth level of knowledge of these artifacts. In this sense, the attempts aimed at integrating digital photogrammetry procedures with non-destructive testing techniques, structural analyses, and virtual reality open the way to really attractive applications [19][20][21]. Another class of examples relies on Building Information Modeling (BIM) and deals with the development of parametric models to enable a digital management of the data resulting from the inspections and maintenance of the assets [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%